Decadal Variation in Raindrop Size Distributions in Busan, Korea. (15th April 2015) - You, Cheol-Hwan; Lee, Dong-In
Abstract : This paper investigated the variability of raindrop size distributions (DSDs) in Busan, Korea, using data from two different disdrometers: a precipitation occurrence sensor system (POSS) and a particle size velocity (Parsivel) optical disdrometer. DSDs were simulated using a gamma model to assess the intercomparability of these two techniques. Annual rainfall amount was higher in 2012 than in 2002, as were the annually averaged D m (which was 0.1 mm greater in 2012) and the frequency of convective rain. Severe rainfall (greater than 20 mm h −1 ) occurred more frequently and with a larger D m in 2012. The values of D m from July, August, and December, 2012, were much greater than from other months when compared with 2002. Larger raindrops contributed to the higher rain rates that were observed in the morning during 2012, whereas relatively smaller raindrops dominated in the afternoon. These results suggest that the increase in raindrop size that has been observed in Busan may continue in the future; however, more research will be required if we are to fully understand this phenomenon. Rainfall variables are highly dependent on drop size and so should be recalculated using the newest DSDs to allow more accurate polarimetric radar rainfall estimation.